Transnacionalismo y género en una comunidad indígena oaxaqueña - Adriana Cruz-Manjarrez (Les Cahiers ALHIM, 2014)
During the past three decades a large number of studies have underlined the importance of gender in shaping migratory processes and the ways in which migration transforms gender roles, relations and ideology. This article examines how gender has structured the international migration of an indigenous Oaxacan community, which has reorganized in transnational social spaces. On the basis of the migration experiences of three generations of Zapotec women who have migrated, this text explores changes in gender relations in marriage, family and the ethnic community in Oaxaca and Los Angeles. It also analyzes why dozens Zapotec men and women who have not migrated argue that migration has freed women migrants. In this study we suggest that Zapotec migration has intersected and intertwined with a series of changes in gender relations and the position of migrant women in the communities of origin and destination. In addition, we argue that migration allowed migrant women in the community of destination to transgress patriarchal power within the family, thus producing in the community of origin the image of the "emancipation" of migrant women.